2016
DOI: 10.4268/cjcmm20160724
|View full text |Cite
|
Sign up to set email alerts
|

Target protein candidates of hypothalamus in aging rats with intervention by Qiongyugao

Abstract: To explore the associated proteins of the hypothalamus in aging rat models with intervention by Qiongyugao(QYG) based on iTRAQ technology, find out the target protein candidates and investigate the mechanism of delaying aging for Qiongyugao. The results showed that Qiongyugao increased GSH-Px activity in serum and SOD activity in liver; the total protein count identified by iTRAQ was 3 522, FDR<1%. There were 20 kinds of differential proteins between the blank group and model group; there were 295 kinds of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Eleven studies have demonstrated the mechanisms underlying the antioxidative activity of KOK. Superoxide dismutase [ 18 – 23 ] and glutathione peroxidase [ 18 – 20 , 22 24 ] showed the highest frequency of activation via antioxidative mechanisms, with 6 studies each. Three studies reported on antioxidative mechanisms through the reduction of reactive oxygen species (ROS).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies have demonstrated the mechanisms underlying the antioxidative activity of KOK. Superoxide dismutase [ 18 – 23 ] and glutathione peroxidase [ 18 – 20 , 22 24 ] showed the highest frequency of activation via antioxidative mechanisms, with 6 studies each. Three studies reported on antioxidative mechanisms through the reduction of reactive oxygen species (ROS).…”
Section: Resultsmentioning
confidence: 99%